School funding formulae: designed to create a learning society?. Issue 4 (4th July 2018) - BenDavid-Hadar, Iris; Case, Stephoni; Smith, Rob
Abstract: The right to education depends upon a willingness to finance education fairly. Addressing the difference in educational achievement between learners of different backgrounds is a key aspect of fairness. Framed by contemporary neoliberal policies around marketisation and competitiveness, this paper examines fairness in the education finance policy (EFP) of three jurisdictions in England, Israel and Oklahoma. Using a comparative analysis of school funding formulae and an international survey on the perceptions of local policy actors, the de jure and the de facto EFPs are examined. Our findings reveal de jure policies attempting to address fairness through integrating different student background characteristics. However, variability is evident in the extent to which the de facto policies align with an aspiration for fairness. This is linked to the marketisation of education in each jurisdiction. We conclude that weightings of students' background characteristics can only be one feature in policy interventions orientated towards bringing about social equity.